PENGARUH PERILAKU MENYIMPANG PESERTA DIDIK TERHADAP PRESTASI BELAJAR DI KELAS VII - Deri Budiman; Okianna Okianna; Mashudi Mashudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
ABSTRACTThis study aims to determine how much influence the student's deviant behavior has on learning achievement in class VII. The research method used is descriptive in the form of quantitative research. The sample in the study was class VII students totaling 31 students who were taken and the data was in the form of a statement questionnaire about deviant behavior with 8 indicators, namely truancy, chatting during class hours, running from school during class hours, not doing school homework, not wearing a belt. or socks, being late, cheating, and dating. Based on the results of the data analysis that the researchers conducted, it was concluded that: 1) deviant behavior resulted in the results of 61.30% (19 students) having a moderate category. 2) Social studies learning outcomes obtained by 74.2% (23 students) have a medium category. 3) the influence of deviant behavior with learning achievement is 0.60 with a standard significant level of 0.05 (5%) So that the results of t count > t table are 9.673> 1.695. From the results of the study, it can be concluded that there is an unfavorable influence between the deviant behavior of students on learning achievement in class VII. In the learning process the greater the deviant behavior, the negative effect on learning achievement as well as the smaller the deviant behavior, the learning achievement will increase.Key Words: Deviant Behavior, Learning Achievement